Generalised single-equation load flow method for unbalanced distribution systems - Segura, S.; da Silva, L. C. P.; Romero, R. [UNESP] (Inst Engineering Technology-iet, 2011)
This study presents a generalised single-equation load flow (GSELF) method for the analysis of unbalanced distribution systems. The proposed method is derived from a recently formulation published in the technical literature, which is based on the impedance matrix and nodal currents injections. The major drawback of this type of method, however, is that the impedance matrix must remain constant throughout the process to guarantee efficiency, thus not allowing the modelling of some of the common components present in distribution networks. This proposal introduces a GSELF method which can overcome this limitation and allow the inclusion of distribution transformers and voltage regulators, in different types of connections, without sacrificing accuracy. Models of distribution system devices such as shunt capacitors and distributed generators, as well as three phase lines and various types of loads can be included. The proposed method is then tested with two benchmark IEEE distribution systems. Results show that the proposed method is effective, computationally robust and faster than the forward/backward sweep method.